Identification of species of emeria of turkeys using regression analysis of morphometric indicators of ocycists - Liulin, Petro; Bogach, Mykola; Getmanets, Oleg (ScienceRise: Biological Science, 2022)
The aim. Identify the species of oocysts of turkeys by morphometric parameters. Material and methods. Eimeria oocysts obtained from faeces of suspects and patients with spontaneous eimeriosis of turkeys of poultry farms of Kharkiv region served as material for the research. Methods used: parasitological, coprological, light microscopy, morphometry, mathematical and statistical, correlation and regression analysis, ANOVA variation statistics. Results. Morphometrically (n=255) samples of turkey eimeria oocysts were studied and identified to the species: E. gallopavonis (n=50), E. meleagrimitis (n=50), E. adenoids (n=51), E. meleagridis n=53), E. innocua (n=51) according to identification indicators (X1 - length of the oocyst in μm; X2 - width of the oocyst in μm; X3 - area of the oocyst in μm; X4 - eccentricity of the model ellipse; X5 - ratio of the width of the oocyst to its length; X6 - largest curvature and X7 - smallest curvature in its model ellipse poles on the major and minor axes, respectively, in μm, X8 - presence - 1 or absence - 0 polar granules) which are mathematical expressions of morphometric dependences of the structure of eocystic oocysts which are confirmed by the results of regression and correlation analysis. The dependence of the Y oocyte species on seven characteristics has been proved. Conclusions. The morphological features that are mathematical expressions of morphometric dependences of the structure and identification of the species of turkey oocysts are determined with high accuracy. The relative error in determining the type of turkey eimerias does not exceed 2 %